Method for efficient determination of material properties for modelling aluminium welding processes: Methode zur effizienten Ermittlung der Werkstoffeigenschaften für die Schweißsimulation von Aluminiumwerkstoffen. Issue 11 (17th November 2016) - Striewe, B.; Seiderer, J.; von Hehl, A.; Repenning, A.; Khazan, P.; Schafstall, H.
Abstract : The trend in the automotive and aircraft industry is moving towards customized designs by using compound structures, which provide an enlarged potential for weight and cost savings. Particularly, thermal joined lightweight structures made of aluminium alloys are characterized by moderate material and processing costs. However, the short and locally focused heat input during welding leads to a degradation of material properties, particularly strength in the heat affected zone (HAZ) of the weld. The need of minimizing of rejections and rework leads to high demands on the welding process. This often requires time‐ and cost‐intensive part testing including accurate determination of the mechanical properties after welding. The prediction of the mechanical properties of welded joints, by means of welding simulation, enables a significant reduction of this time‐ and cost‐intensive testing effort. However, the application of such a model requires a sufficient base of material data, which has usually to be generated by an extensive testing procedure for each single alloy. Against this background, a new method for an efficient determination of material properties for the simulation of thermal joining processes of age‐hardenable aluminium alloys was developed within the programme of the research project.